Postur Kerja dan Gangguan Otot Rangka Akibat Kerja Pada Juru Las - Lestari, Kartika Dani; Hendra, Hendra (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Welding work is one of the occupations that has the potential to cause musculoskeletal disorders (MSDs) complaints due to non-ergonomic work postures. Welders tend to make odd and repetitive movements by 80.8% so they might potentially cause them to experience MSDs.This study aims to assess the risk of ergonomics in welding work at PT X's workshop A and its correlation with welder’s complaints of MSDs. This study used a cross-sectional design. Observations of the work process and interviews were carried out from January 18 to February 1, 2022 using the Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM). Most of the welders performed welding in a squatting posture (72.4%), followed by a standing and sitting posture. The results of the ergonomic risk level assessment showed that the squatting posture had a very high risk level. Meanwhile, the dominant complaints filed by welders were the lower back (59%) and neck (45%). Improvement efforts are urgently needed to reduce the level of risk and complaints of MSDs from welders by implementing the Health Risk Assessment (HRA) program as the first step to determine an occupational health service program for workers.